Has political correctness gone mad? Trevor Phillips and the backlash thesis - Pilkington, Andrew (Advances in Social Sciences Research Journal, 2021)
The concept of political correctness, or more accurately, anti-political correctness has re-emerged in the last decade as a major interpretive framework in the media. Populist politicians such as Trump in the US and Farage (a key advocate of Brexit) and Johnson in the UK for example routinely draw upon a discourse featuring political correctness as a bete noire. While the attack on PC is typically made by conservatives, I focus in this paper on a left wing critic, Trevor Phillips who argues that the prevasiveness of PC has fueled a populist backlash. It is argued, contrary to Phillips, that it is not PC but an anti-PC discourse that lies behind the success of populist politicians in the UK and US and that the campaign against political correctness plays well with their supporters.